2017
DOI: 10.3892/ijo.2017.4072
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-379 inhibits metastasis and epithelial-mesenchymal transition via targeting FAK/AKT signaling in gastric cancer

Abstract: Accumulating evidence demonstrates that aberrant miRNAs contribute to gastric cancer (GC) development and progression. However, the roles of various miRNAs in GC remain to be determined. In the present study, we confirmed that a reduced miR-379 expression was present in GC tissues and cell lines. Our clinical analysis revealed that the downregulated miR-379 expression was significantly correlated with poor prognostic features including lymph node metastasis and advanced TNM stage. Moreover, we confirmed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Many targets of miR‐379 have been confirmed. For example, FAK was found in gastric cancer and hepatocellular carcinoma, cyclin B1 in breast cancer, and MDM2 in bladder cancer . In the present study, TCF‐4 was detected as a direct target of miR‐379 in laryngeal carcinoma and validated by luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Many targets of miR‐379 have been confirmed. For example, FAK was found in gastric cancer and hepatocellular carcinoma, cyclin B1 in breast cancer, and MDM2 in bladder cancer . In the present study, TCF‐4 was detected as a direct target of miR‐379 in laryngeal carcinoma and validated by luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 61%
“…Many targets of miR-379 have been confirmed. For example, FAK was found in gastric cancer 31 and hepatocellular carcinoma, 29 cyclin B1 in breast cancer, 18 and MDM2 in bladder cancer. 32 In the present F I G U R E 4 TCF-4 overexpression rescued the tumor-suppressing roles of miR-379 on laryngeal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-29 family, consisting of miR-29a, miR-29b and miR-29c, was able to restrain Akt2 expression and subsequently inactivate GSK3β, leading to the impaired invasive ability of GC cells (62). Focal adhesion kinase (FAK) is a crucial transducer of integrin-mediated signaling to downstream pathways, including the PI3K/Akt pathway (63). The activated FAK by integrins may form a binding site for the SH2 domain of p85 subunit and phosphorylate it, which may subsequently activate the p110 catalytic subunit of PI3K (63).…”
Section: Regulation Of Mirnas On the Pten/pi3k/akt Pathway In Gcmentioning
confidence: 99%
“…The activated FAK by integrins may form a binding site for the SH2 domain of p85 subunit and phosphorylate it, which may subsequently activate the p110 catalytic subunit of PI3K (63). Xu et al (63) identified that miR-379 inactivated Akt signaling by suppressing FAK expression, thus leading to inhibition of cell migration, invasion and EMT process. Cullin 4B, a scaffold protein, directly binds to the S2 region of the miR-125a promoter and transcriptionally represses miR-125a, through which it promotes HER2 expression, thus stimulating downstream PI3K/Akt signaling and the migration of GC cells.…”
Section: Regulation Of Mirnas On the Pten/pi3k/akt Pathway In Gcmentioning
confidence: 99%